DEPRESI DALAM NOVEL â€œROOMâ€ By Emma Donnoghue - Lengkong, Elisa Mariam (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT â€œRoomâ€ is a national best seller novel written by Emma Donoghue. It tells a story about a child, Jack ,and his mother, Joy, that were caged in a room by a man who kidnapped and raped Joy, long before JackÂ  born. The novel is told from Jackâ€™s point of view. This research aims at identifying, analyzing and describing the depression in â€œRoomâ€. And also the causes and effects of the depression which are described in this novel. The identification of the data are based on Â the theory about Literature. The data are taken from the novel. Â Furthermore, there will be an analyzis using the psychological perspective from the Â theory of Wellek and Warren (1997). In analyzing the data, the writer uses intrinsic and extrinsic approaches. The writer collected data which were taken from the novel, by reading carefully and underline the things that depict important events in â€œRoomâ€, as well as notes or summaries that can support the research. The process of data collection is done through the identification of the psychological aspects in the novel and the data ware analyzed to find out the causes of Jackâ€™s and Joyâ€™s depression. The result of this research shows that depression picture true Jack and Joy, they experienced some horrible event, where they have been lock up in a room, theÂ Â Â Â Â  cause of the lock up made Jack anti-social and Joy hurts her child, and try to kill herself. Â  Key words: Literature, Novel, Room, Depression, Psychological Analysis.